Method for the improvement of mechanical properties of biodegradable polymeric scaffolds - Schümann Kerstin; Arbeiter Daniela; Grabow Niels; Schmitz Klaus-Peter (Current Directions in Biomedical Engineering, 2019)
At present, a main focus in the field of stent technologies is on the development of biodegradable polymeric stents. Due to inferior material characteristics of polymers compared to permanent metals stents require thicker stents struts to accomplish adequate mechanical properties. Therefore, a thermo-mechanical treatment of polymeric stents was tested, which showed a positive effect on mechanical stent characteristics.